Tinjauan Yuridis Pembatalan Perjanjian Secara Sepihak Menurut Peraturan Perundang-Undangan - VENDI, VENDI SUGARA (Universitas Medan Area, 2024)
The aim of this research is to discuss unilateral cancellation of an agreement in an agreement, unilateral cancellation is considered an unlawful act or breach of contract and the juridical implications of an agreement that is canceled unilaterally. This type of research approach uses normative research studies which examine several statutory regulations. The results of the discussion in this research state that unilateral cancellation of an agreement is not permitted according to statutory regulations, it is only permitted if there is a court decision that has permanent legal force. Regarding the juridical legal implications of unilaterally canceled agreements, there is actually a legal vacuum in the legal system in Indonesia. The judge who decided this case only used the jurisprudence of Supreme Court Decision No. 4/Yur/Pdt/2018 as a legal source in deciding that unilateral cancellation was an unlawful act. If we refer to jurisprudence, of course this cannot be fully justified, because Indonesia adheres to a civil law legal system or a written legal system. Meanwhile, jurisprudential legal sources are only used by countries that adhere to common law.